Quantification of Interfacial Charges in Multilayered Nanocapacitors by Operando Electron Holography - Zhang, Leifeng (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.